Utilizing STEM-based practices to enhance mathematics teaching in Vietnam: Developing students' real-world problem solving and 21st century skills - Hoa Anh Tuong; Pham Sy Nam; Nguyen Huu Hau; Vo Thi Bich Tien; Zsolt Lavicza; Tony Hougton (OmniaScience, 2023)
In Vietnam, STEM-based teaching approaches have been recommended for schools since 2018 with the integration of multiple related courses in schools. Teachers' perspectives on integrated STEM education, and how to design a STEM lesson that supports students' learning are critical for ensuring that an integrated STEM curriculum is implemented successfully. This paper aims to describe a study applied successfully to STEM education in teaching Mathematics, in particular "Trigonometry ratio of an acute angle" in Vietnam.  This study utilized mixed methods approaches with three phases: the first stage employed a quantitative study to examine the Vietnamese teachers' perspectives on STEM education. The second phase was an experiment on teaching while applying STEM education to design and organize a mathematics lesson, and the final phase was to employ a qualitative study to explore the Vietnamese students' experiences of STEM education connected with real-world problem solving and 21st-century skills development. A total of 47 teachers and 85 students participated in this study and data was collected through multi ways of surveys and semi-structured interviews. The findings show Vietnamese teachers' perspective of the necessity and importance of applying STEM education, however, they reported facing many challenges. A lesson designed as a STEM education application and the student's feedback regards the real-world roles. Learning outcomes connect with 21st-century skills in this study that are expected to provide the success evidence for further discussion and practice to improve the effectiveness of teaching and learning STEM education in Vietnam